"We are Motor Men": Management culture and consciousness in the South African motor industry - Duncan, David (My University, 1992)
This paper is part of a research project on the history of the motor industry in South Africa from the 1920s to the present. The broader study looks at all aspects of the industry, from government policy, through foreign and local investment, to the organisation of production and labour relations. It takes in both the assembly sector (or, as they prefer to be called, the vehicle manufacturers) and the components sector (the parts manufacturers). Research in the social sciences has tended to be polarised between analyses of resistance against the apartheid regime and studies of the state itself. Where academic treatises have broached the topic of industry, it has been the owners of the means of production, the capitalists themselves, who have constituted the focus of attention. This essay deals mainly with the next rung in the business ladder - the senior and middle managers who actually run capitalist enterprises from year to year. It attempts a general survey of the historical development of management culture and attitudes in the motor industry. A later paper will compare and contrast these attitudes with those of shop floor workers.
African Studies Seminar series. Paper presented 11 May, 1992
Keywords: Automobile industry and trade. South Africa. Management